Comparision of the efficacy and safety between Secukinumab and Adalimumab in the treatment of the moderate to severe plaque psoriasis - Dandan HU; Peimiao ZHANG (Pifu-xingbing zhenliaoxue zazhi, 2023)
Objective To evaluate the efficacy and safety of Secukinumab versus Adalimumab in the treatment of the moderate to severe plaque psoriasis. Methods A total of 90 patients with moderate to severe psoriasis were randomly divided into three groups: Secukinumab group (30 patients), Adalimumab (29 patients) and conventional therapy groups (31 patients). The Secukinumab and Adalimumab groups were treated with Secukinumab and Adalimumab, respectively, while conventional therapy group was treated with conventional medication (Acitretin, compound glycyrrhizic anhydride, calcipotriol and halometasone ointment). The PASI and PASI50/75/90/100 were evaluated at the 0th, 4th, 8th and 12th week of treatment. The DLQI were assessed at the 0th and 12th week. In addition, the safety was assessed after the treatment. Results ① The PASI and DLQI scores were lower and the improvement rates of PASI and DLQI were higher in both the secukinumab-and Adalimumab-treated groups than in the conventional medication-treated group after 4, 8 and 12 weeks of treatment (P<0.05). But PASI and DLQI scores, and the improvement rates of PASI and DLQI did not differ significantly between the Secukinumab-treated and Adalimumab-treated group (P>0.05). ② PASI50/75/90/100 responses were similar among the three groups at the 4th week. However, PASI50/75/90/100 responses were higher in both the Secukinumab- and Adalimumab-treated groups than that in the conventional medication-treated group at the 12th week (P<0.05). Again, PASI50/75/90/100 responses were comparable between the Secukinumab- and Adalimumab-treated groups. The incidence of adverse did not differ among the three groups (P>0.05). Conclusions Secukinumab and Adalimumab are more effective than the conventional medication for the moderate to severe plaque psoriasis. The efficacy of Secukinumab is comparable to that of Adalimumab.